(untitled) - University of Cambridge ESOL examinations (England, 2017)
Cambridge IELTS 3 provides students with an excellent opportunity to familiarise themselves with IELTS and practise examination techniques using authentic test material. This collection includes practice in the updated Speaking test (June 2001 syllabus), plus extra Reading and Writing modules for General Training candidates. The book includes an introduction to these different modules together with an explanation of the scoring system used by Cambridge ESOL. The comprehensive section of answers and tapescripts means that the material is ideal for students working partly or entirely on their own.
Keywords: Anh ngữ,English language; Giáo trình cho người nước ngoài,Textbooks for foreign speakers